Shared Solar Generation and Battery Storage Systems in Residential Microgrids - Syed, Moiz Masood (Curtin University, 2021)
This thesis presents investigation on performance analysis, technical benefits and challenges on deployment of shared energy microgrid in an Australian apartment precinct at WGV. Performance analysis was conducted to examine load profiles of apartment units and impact of renewable installation was analysed in terms of grid reliance reduction. The shared configurations implemented in three different apartment complexes and analysed dataset from these systems and buildings presents a significant contribution to the research.